2016
DOI: 10.1080/02699931.2016.1268998
|View full text |Cite
|
Sign up to set email alerts
|

Moment-to-moment changes in feeling moved match changes in closeness, tears, goosebumps, and warmth: time series analyses

Abstract: Feeling moved or touched can be accompanied by tears, goosebumps, and sensations of warmth in the centre of the chest. The experience has been described frequently, but psychological science knows little about it. We propose that labelling one's feeling as being moved or touched is a component of a social-relational emotion that we term kama muta (its Sanskrit label). We hypothesise that it is caused by appraising an intensification of communal sharing relations. Here, we test this by investigating people's mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
168
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(187 citation statements)
references
References 34 publications
16
168
0
3
Order By: Relevance
“…The difference from the kama muta model is best illustrated with an example. As we know from another study (Schubert et al, 2016), the peak of the kama muta experience in the lion video (one of the four videos presented in all five countries) occurs when a lion that had been saved and raised by two young men, and then released in Africa, later recognizes them in the wild, runs toward them, and hugs them repeatedly. We think this act exemplifies communal sharing by showing closeness through a joyous reunion with hugging, laughing, and relief, rather than a virtuous act by the lion or by the men at that moment.…”
Section: Appraisalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference from the kama muta model is best illustrated with an example. As we know from another study (Schubert et al, 2016), the peak of the kama muta experience in the lion video (one of the four videos presented in all five countries) occurs when a lion that had been saved and raised by two young men, and then released in Africa, later recognizes them in the wild, runs toward them, and hugs them repeatedly. We think this act exemplifies communal sharing by showing closeness through a joyous reunion with hugging, laughing, and relief, rather than a virtuous act by the lion or by the men at that moment.…”
Section: Appraisalsmentioning
confidence: 99%
“…Research assessing moving or touching experiences has been conducted using U.S. American (Schubert, Zickfeld, Seibt, & Fiske, 2016;Thomson & Siegel, 2013), British (Schnall & Roper, 2012;Schnall et al, 2010), French-speaking Swiss (Cova & Deonna, 2014), German (Kuehnast et al, 2014;Menninghaus et al, 2015;Wassiliwizky, Jacobsen, Heinrich, Schneiderbauer, & Menninghaus, 2017), Japanese (Tokaji, 2003), Dutch (Strick et al, 2015), Norwegian (Seibt, Schubert, Zickfeld, & Fiske, 2017), and Finish (Vuoskoski & Eerola, 2017) participants. Yet each of these studies has used different elicitors and different methods, so, to date no study has systematically compared responses to moving stimuli with the same measures across a range of cultures.…”
Section: Being Moved: Phenomenology Elicitors and Outcomesmentioning
confidence: 99%
“…The third bodily sensation that has been reported repeatedly across the literature is the experience of warmth, especially in the center of the chest (Cova & Deonna, 2014;A. P. Fiske, Schubert, et al, 2017a;Pohling & Diessner, 2016;Schnall et al, 2010;Schubert et al, 2016;Tan & Frijda, 1999;Thomson & Siegel, 2016;Zickfeld, 2015). It is not clear whether there is an actual physical increase of warmth in the body, especially since many people experiencing kama muta on many occasions report a pleasant feeling in the center of the chest that they describe as something other than warmth, such as swelling or tingling or some kind of motion.…”
Section: Bodily Reactionsmentioning
confidence: 98%
“…A second bodily reaction that has been mentioned frequently is goosebumps or chills (we provisionally treat them here as two names for the same experience, although they may be distinct; Benedek & Kaernbach, 2011;A. P. Fiske, Schubert, et al, 2017a;Konečni, 2005;Menninghaus et al, 2015;Mori & Iwanaga, 2017;Panksepp, 1995;Schubert et al, 2016;Wassiliwizky et al, 2015). Panksepp (1995) found self-reports of chills in the context of music (see also Laeng, Eidet, Sulutvedt, & Panksepp, 2016;Mori & Iwanaga, 2017;Nusbaum et al, 2014), which has been found to evoke being moved quite frequently (Juslin & Laukka, 2004).…”
Section: Bodily Reactionsmentioning
confidence: 99%
“…They also showed convergent validity in the form of associations with various multiple-item inventories, and applicability across different cultures (Dalsky, Gohm, Noguchi, & Shiomura, 2008;Gächter, Starmer, & Tufano, 2015;Li, 2002). The IOS scale has also been linked to one relational model proposed in relational models theory (RMT, Fiske, 2004), namely communal sharing, which highlights the common and shared essences of individuals and is subjectively experienced as closeness (Schubert, Zickfeld, Seibt, & Fiske, 2016).…”
Section: Explicit Measures Of Iosmentioning
confidence: 99%